Using biometrics and active RFID to improve security and safety in mass casualty management. (1st January 2012) - Xiao, Qinghan; Wilkinson, Diana; Anderson, Malcolm
In a mass casualty incident, it is necessary to control the access to the incident-site to maintain site security and to obtain accurate and real-time incident data. Currently, first responders are identified by their badges and/or uniforms, and may need to on-scene-triage patients using a tag-classification system. Potential security and safety problems may develop because the badges could be duplicated or cloned, uniforms could be found at thrift stores, and the paper tags may have limitations in preserving information during documentation. In this paper, we present a combined approach that uses biometric technology to verify the identity of first responders and radio frequency identification (RFID) technology to assist in triage of mass casualty victims. In contrast to other proposals that recommend smart cards to carry biometric data and use passive RFID tags as triage tags; we propose using active RFID wristband to perform both verification and triage functions.